Penerapan Pesan Literasi Media oleh Perempuan dalam Keluarga (Studi Terhadap Keluarga di Kota Kupang) - Ferly Tanggu Hana; Struce Andriyani (Jurnal Communio : Jurnal Jurusan Ilmu Komunikasi, 2018)
This study is focused on identifying domestic media literacy messages of families in Kupang City. The author was interested in figuring out the application of media literacy messages by women (housewives) within family. The research question for this study was: How is the application of media literacy messages by women in families in Kota Kupang, NTT?. The aim to be achieved was to find out the application of media literacy messages by housewives in the family. The method used was in-depth interviews with housewives in various professions and educational backgrounds in Kota Kupang, NTT. The results of the study showed that media literacy messages have been conveyed in the informants' families, such as rules of media consumption either through TV or the Internet. These messages were dominated time constraint on watching TV or accessing Internet and the selection of certain broadcast contents. However, assisting process which is actually an important part of the media literacy process has not been applied by the informants. Keywords: Communication, Housewives, Media Literacy, Family